2010
DOI: 10.1109/tia.2010.2057494
|View full text |Cite
|
Sign up to set email alerts
|

A Small Segmented Oscillating Water Column Using a Savonius Rotor Turbine

Abstract: Abstract-This paper outlines a project which addresses the use of a small segmented oscillating water column with three sections. The turbine utilises cascaded Savonius rotors (one for each section) and this system is developed and tested for validation of the performance algorithms. It is shown that the systems can be easily described and a system developed that can generate. It would be suitable for a shoreline location such as a harbour wall, where waves are random and not orthogonal to the column. Conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Therefore this makes too great interest in order to apply the plant here. Up today many researches and tests have been done for improving Wells turbine [13], [14]. Thus, to the realized tests and researches mainly on the Northern sea coast so, England, Denmark, Germany and other European countries testing and experimental investigations are being carried out.…”
Section: Energy Analysismentioning
confidence: 99%
“…Therefore this makes too great interest in order to apply the plant here. Up today many researches and tests have been done for improving Wells turbine [13], [14]. Thus, to the realized tests and researches mainly on the Northern sea coast so, England, Denmark, Germany and other European countries testing and experimental investigations are being carried out.…”
Section: Energy Analysismentioning
confidence: 99%
“…7, which influences the natural frequencies of all chambers. The mean wave height across the side face of the column [20][ 21] can be described by…”
Section: Wave-power Absorption By An Mcowcmentioning
confidence: 99%
“…The second term of the absorbed power due to change air pressure (P P ), which can be represented as [20]:…”
Section: Wave-power Absorption By An Mcowcmentioning
confidence: 99%
“…A study (before 2010) showed that there were over 1000 patented ideas for wave energy conversion. Among different technology groups OWC is a very straightforward device consisting of two basic part: 1) the chamber; and 2) the turbine [5] Multi chamber or segmented OWC has been studied briefly in [6] Performance of the turbines like savonious or wells and effect of guided vanes on wells turbine used in OWC, have also been matter of research. [6,7,8] …”
Section: Related Workmentioning
confidence: 99%